Bridging Chiral de‐tert‐Butylcalix[4]arenes: Diastereomeric Crystallization‐Based Optical Resolution and Determination of Absolute Configuration. Issue 36 (25th September 2018) - Liu, Wen‐Shan; He, Di; Ma, Hao; Weng, Xiu‐Fang; Ren, Shan‐Shan; Liu, Xiong; Tang, Sheng‐An; Ma, Shi‐Kun; Liu, Jun‐Min; Li, Shao‐Yong
Abstract: A pair of diastereomers2 a and2 b were synthesized from the conjugation of bridging chiral de‐tert‐ butylcalix[4]arene racemate1 and (1 S )‐(+)‐10‐camphorsulfonyl chloride. The diastereomeric separation by crystallization was explored in different solvents, temperature and time. The optimal crystallization procedures can afford them in a desirable yield, de and purity. A pair of enantiomers1 a and1 b were subsequently obtained after their hydrolysis. Moreover, their absolute configurations were determined by X‐ray crystallographic analysis. The crystallization results can match the large‐scale preparation of optically pure de‐tert ‐butylcalix[4]arene in laboratory and industry. Abstract : A pair of diastereomers 2a and 2b were successfully separated by crystallization in a desirable yield, de and purity. Subsequently, a pair of enantiomers can be obtained after their hydrolysis. Moreover, their absolute configurations were determined by X‐ray crystallographic analysis.